2019
DOI: 10.1080/13557858.2019.1613519
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding obstetrical interventions among US-based Somali migrant women: a qualitative study

Abstract: Yet unknown is how they avoid obstetrical 17 interventions. This study sought to identify perceived protective mechanisms used to avoid obstetric 18 interventions as well as the underpinning factors that influence aversion to obstetrical interventions by 19 Somali refugee women. 20 Design: A descriptive, exploratory qualitative study purposively sampled Somali refugee women recruited 21 via snowball technique in Franklin County, Ohio, United States. Data was collected through audio-22 recordings of individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 38 publications
1
59
0
Order By: Relevance
“…There is also a need for a structure to how this information is given and for adaptation regarding content and format. Group information and video training specifically for Somali women were appreciated by the women as these improved their care satisfaction through providing increased knowledge and reduced stress [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…There is also a need for a structure to how this information is given and for adaptation regarding content and format. Group information and video training specifically for Somali women were appreciated by the women as these improved their care satisfaction through providing increased knowledge and reduced stress [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Many women who had migrated to high- or middle-income countries expressed satisfaction with their maternity care overall, but this was usually framed in contrast to their previous maternity experiences in resource-poor settings with higher maternal mortality rates and gratitude for being taken care of within the host country health system ( Riggs et al., 2017 ; Niner et al., 2013 ; Korukcu et al., 2018 ; Henry et al., 2020 ; Bader et al., 2020 ; LaMancuso et al., 2016 ). In spite of this satisfaction, women in many studies identified being stigmatised and receiving disrespectful or discriminatory care, due to being foreign, their skin colour, immigration status or being unable to speak the host-country language ( Riggs et al., 2017 ; Chulach et al., 2016 ; Niner et al., 2013 ; McLeish, 2005 ; Lalla et al., 2020 ; Herrel et al., 2004 ; Agbemenu et al., 2019 ). They felt their needs were disregarded, they were treated rudely or as inferior to host-country women and, particularly with reference to female genital mutilation (FGM), put on display and ‘othered’ ( Stapleton et al., 2013 ; Agbemenu et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…In spite of this satisfaction, women in many studies identified being stigmatised and receiving disrespectful or discriminatory care, due to being foreign, their skin colour, immigration status or being unable to speak the host-country language ( Riggs et al., 2017 ; Chulach et al., 2016 ; Niner et al., 2013 ; McLeish, 2005 ; Lalla et al., 2020 ; Herrel et al., 2004 ; Agbemenu et al., 2019 ). They felt their needs were disregarded, they were treated rudely or as inferior to host-country women and, particularly with reference to female genital mutilation (FGM), put on display and ‘othered’ ( Stapleton et al., 2013 ; Agbemenu et al., 2019 ). “I feel like that doctor did not look after me very well… I am not sure if it is because we are refugees that they don't treat us very well.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Paternal origin was unregistered in as many as 1 in 5 births to women originating from sub-Saharan Africa. It is possible that a lack of information about fathers of the babies of sub-Saharan African women and their poorer outcomes might be explained by more limited health literacy [ 50 ], distrust in the healthcare system [ 51 , 52 ], or a delay in seeking antenatal care [ 52 54 ]. This might also be the case for other migrant women, such as those who have fled from wars and conflicts [ 44 ].…”
Section: Discussionmentioning
confidence: 99%